Re-visiting the strategy-performance question: An empirical analysis - O’Regan, Nicholas; Ghobadian, Abby (International Journal of Management and Decision Making, 2004)
Strategic planning is assuming a greater importance for small- and medium-sized manufacturing firms as well as large firms. However, the lack of systematic strategic planning is considered by some commentators to be major reason for the failure of many of the initiatives designed to make SMEs more competitive. This paper reports the results of a nation-wide survey conducted in the UK, investigating the association between the emphasis placed on factors shaping the strategic plan together with their attendant resources and their perceived impact on a range of tangible and intangible performance measures. Evidence gathered suggests that a positive relationship exists between some dimensions of performance and a number of these factors. The analysis also indicates that high-performing firms place a greater emphasis on each of these factors compared with low-performing firms. Â© 2004 Inderscience Enterprises Ltd.
Keywords: Innovation; Operations Management and Supply